Sensitizing the therapeutic efficacy of taxol with shikonin in human breast cancer cells. - Wenjuan Li; Joan Liu; Kasey Jackson; Runhua Shi; Yunfeng Zhao (PLoS ONE)
Shikonin, a small-molecule natural product which inhibits the activity of pyruvate kinase M2 (PKM2), has been studied as an anti-cancer drug candidate in human cancer models. Here, our results demonstrate that shikonin is able to sensitize human breast cancer cells to chemotherapy by paclitaxel (taxol). Human breast adenocarcinoma MBA-MD-231 cells, which have higher levels of PKM2 expression and activity compared with MCF-7 cells, were selected to study further. The concentrations of shikonin and taxol were first selected at which they did not significantly induce cytotoxicity when treated alone, whereas the combination induced apoptosis. Surprisingly, PKM2 activity was decreased by shikonin, but not by the combination treatment. To identify the potential targets of this combination, human phospho-kinase antibody array analysis was performed and results indicated that the combination treatment inhibited the activation of ERK, Akt, and p70S6 kinases, which are known to contribute to breast cancer progression. Finally, how the combination affects breast cancer cell growth in vivo was tested using a xenograft tumor model. The results indicated that shikonin plus taxol prolonged animal survival and reduced tumor size than the vehicle treatment group. In summary, our results suggest that shikonin has a potential as an adjuvant for breast cancer therapy.